If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9 + 2x + 4x = 57 Combine like terms: 2x + 4x = 6x -9 + 6x = 57 Solving -9 + 6x = 57 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + 6x = 57 + 9 Combine like terms: -9 + 9 = 0 0 + 6x = 57 + 9 6x = 57 + 9 Combine like terms: 57 + 9 = 66 6x = 66 Divide each side by '6'. x = 11 Simplifying x = 11
| 1-2m+1=-2 | | 6(3x-2)+4x=0 | | 28-k=-7(k-4) | | 15(2)-10=20 | | -73x+87.93759-84.8385827x=8365936 | | .25x+13=.5x-8 | | Y-8x=4 | | 183x-5= | | -2(t+2)=6t+11 | | 3w-9=9 | | 8x-3(-5x+2)=40 | | 4R-1=27 | | 5p-14=5p+4+13p | | 3(x+5)=3x+12 | | 0.6w=0.666 | | -18+36y=-15 | | 56-2x=10x+12 | | 7+3r=13 | | 6u-8=25 | | 2x^2+7x=4x+9 | | 3(x-4)=5x-2x-12 | | 11x=14x-15 | | x^2+7x=-20 | | 2ab-3c= | | 2x^2+12x=5x+4 | | 0=x^2+12x-49 | | 7x+85.73-8.33x=5.85 | | -2x+15=-4x-3 | | 16=3g+10 | | 16=18c+32 | | 2x+111=6x-9 | | 18h^2-27h-5=0 |